A Rare Case of Bronchial Anthracofibrosis with Pleural Anthracosis Presented as Recurrent Pleural Effusion - Rajesh Kumar Yadav; Jitendra Kumar Saini; Prabhpreet Sethi; Rohit Sarin (Case Reports in Pulmonology)
A fifty-eight-year-old, nonsmoker Indian male presented with recurrent left pleural effusion. He had history of dry cough, exertional breathlessness for the last two years. He denied any occupational exposure or second hand smoke exposure. His physical examination demonstrated decreased breath sounds on the left side of chest. Cardiac evaluation was unremarkable. Diagnostic pleural aspiration revealed straw coloured fluid, exudative, and nonmalignant in nature. CT-imaging of the chest demonstrated left pleural effusion, nodular parenchymal infiltrates in bilateral lungs, plate like atelectasis in the left lower lobe. Bronchoscopy showed diffuse airway pigmentation, right middle lobe opening, and left lower lobe bronchus pigmented and stenosed. Semi-rigid pleuro-videoscopy revealed diffuse black coloured deposits over visceral pleura and focally scattered deposits over parietal pleura. Spirometry showed mild airway obstruction with moderate impairment in diffusion capacity.